O ensino da função quadrática através de diferentes atividades práticas elaboradas para o ensino médio - Braçale, Vinicius Cesar (2024)
Using practical methodologies in the classroom, this work presents a set of three activities to be applied in the classroom to assist in teaching quadratic functions in basic education. Each activity proposes to use a different methodological approach, the first being the realization of a game built in the GeoGebra software, the second a mathematical modeling on the oblique launch, and the last a practical activity proposing an investigation of the reflective property of the parabola through of constructing an experiment. The main objective of the sequence of activities presented here is to build material that can be used by mathematics teachers to teach this topic in different realities. The work presents a bibliographical research on the topic, addressing the theory necessary to understand the subject, and also describes the carrying out of qualitative research on one of its activities that was applied to a third-year high school class at a public school. In view of the analysis of the results, it can be seen that the application of the activity created a learning situation in which students were able to understand the quadratic function applied to a real situation, in the process they improved cooperation and teamwork skills, logical reasoning, in addition to recovering the concepts of the quadratic function. Thus, it was possible to understand how activities developed by active methodologies can construct different learning situations that stimulate the teaching of mathematics.